Detection of Thrombi in Left Atrial chamber by Transoesophageal Ecchocardiography in patients suffer from Non-rheumatic Atrial Fibrillation - Khalaf, . Khalil Sarhan; Haji, .Ghazi F.; Mahmood, . Ghassan M.; Naser, Nazar (AL-Kindy College Medical Journal, 2016)
Background: Background : Patients with non-rheumatic atrial fibrillation have high risk of thromboembolism especially ischemic stroke usually arising from left atrial appendage .Transoesophageal echocardiography provides useful information for risk stratification in these patients as it detects thrombus in the left atrial or left atrial appendage. Objective : This study was conducted at Al-Kadhimiya Teaching Hospital to assess the prevalence of left atrial chamber thrombi in patients with chronic non-rheumatic atrial fibrillation using transoesophageal echocardiography and its clinical significance as well as to verify the superiority of transoesophageal over transthoracic echocardiography in the detection of these abnormalities. Type of the study: Cross sectional study.Patients and Methods : Forty (40) consecutive patients (11 female and 29 male), at a mean age of 46 ± 9 years (range 28–60) with chronic non-rheumatic Atrial fibrillation were enrolled to this prospective study between March 2006 and December 2006. Tansthoracic and transesophageal two dimensional , M- mode , Doppler, and color- flow echocardiography were obtained with a kretz diagnostic ultrasound system. Results : The prevalence of Left atrium thrombus was 12.5%, 5 patients from the total number which was 40 patients. All of them seen bytransoesophagealechocardiography and non are detected byTansthoracic echocardiography . All the left atrial thrombi were confined to the left atrial appendage (100%). Left atrial spontaneous echo contrast was detected in 10 patients 25% by transoesophageal echocardiography, but was not observed in patient bytransthoracic echocardiography. All the 5 thrombi were found in left atria were significantly associated with spontaneous echo contrast 100% (P-value <0.001), reduced left ventricle ejection fraction (p-value <0.05) , large left atrium diameter ( p-value <0.05) and low LAAV <20 cm/s (p-value <0.001) compared to those without thrombus . Conclusions : The study showed that the prevalence of left atrial thrombus and appendage is not uncommon in patients with non-rheumatic atrial fibrillation and is exclusively seen in patients with left atrial SEC. Low Left ventricle ejection fraction , large Left atrium diameter , and low Left atrial appendages velocity are significantly associated with subsequent thrombus formation , and is more sensitive in the detection of these abnormalities compared with transthoracic echocardiography